2006
DOI: 10.1111/j.1399-3054.2006.00658.x
|View full text |Cite|
|
Sign up to set email alerts
|

Dual function of pyrimidine metabolism in potato (Solanum tuberosum) plants: pyrimidine salvage and supply of β‐alanine to pantothenic acid synthesis

Abstract: Uridine and cytidine are major nucleosides and are produced as catabolites of pyrimidine nucleotides. To study the metabolic fates and role of these nucleosides in plants, we have performed pulse (2 h) and chase (12 h) experiments with [2-14 C]uridine and [2-14 C]cytidine and determined the activities of some related enzymes using tubers and fully expanded leaves from 10-week-old potato plants (Solanum tuberosum L.). In tubers, more than 94% of exogenously supplied [2-14 C]uridine and [2-14 C]cytidine was conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…In animals, the catabolic pathway is the sole route for β-alanine synthesis ( Traut & Jones, 1996 ), but, in plants, β-alanine production from polyamine oxidation ( Terano & Suzuki, 1978 ) or other processes may be more important. Recently, Katahira & Ashihara (2006 ) have reported that [U- 14 C]-Ura is extensively degraded to 14 CO 2 in potato leaf tissues (37% total incorporated label). Although 8% of the label resided in β-alanine, only 1% of the radioactivity occurred in pantothenate and 21% of the label was found in common amino acids, presumably derived from labelled C-skeletons produced by BAT reaction (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In animals, the catabolic pathway is the sole route for β-alanine synthesis ( Traut & Jones, 1996 ), but, in plants, β-alanine production from polyamine oxidation ( Terano & Suzuki, 1978 ) or other processes may be more important. Recently, Katahira & Ashihara (2006 ) have reported that [U- 14 C]-Ura is extensively degraded to 14 CO 2 in potato leaf tissues (37% total incorporated label). Although 8% of the label resided in β-alanine, only 1% of the radioactivity occurred in pantothenate and 21% of the label was found in common amino acids, presumably derived from labelled C-skeletons produced by BAT reaction (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the course of pyrimidine catabolism, [ 14 C] β‐UP is hydrolysed to 14 CO 2 , NH 3 and β‐alanine. Because radioactivity from [2‐ 14 C]pyrimidine precursors was not incorporated into β‐alanine, we were not able to follow the metabolic fate of β‐alanine, but this compound is a starting material for the synthesis of various compounds, including pantothenic acid and coenzyme A (Katahira and Ashihara 2005). In Limonium latifolium , which is a halotolerant, β‐alanine derived from uracil is utilised for the synthesis of β‐alanine betaine (Duhazé et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Increases of cytidine and guanosine were observed in transgenic samples. The accumulation of both nucleosides has been previously related to a decrease in the activity of uridine/cytidine kinase . As a consequence of this decrease, this substrate cannot be converted into of β‐ureidopropionic acid, carbon dioxide (CO 2 ), β‐alanine, pantothenic acid and several common amino acids .…”
Section: Resultsmentioning
confidence: 99%
“…The accumulation of both nucleosides has been previously related to a decrease in the activity of uridine/cytidine kinase . As a consequence of this decrease, this substrate cannot be converted into of β‐ureidopropionic acid, carbon dioxide (CO 2 ), β‐alanine, pantothenic acid and several common amino acids . These experimental results coincide with those of in silico predictions, which strongly indicate an affectation of alanine, aspartate and glutamate metabolism (Figure S1).…”
Section: Resultsmentioning
confidence: 99%